Mediastinal and Retropharyngeal Abscesses in a Neonate - Chien-Han Chen; Chao-Jan Wang; Reyin Lien; Yi-Hung Chou; Chien-Chih Chang; Ming-Chou Chiang (Elsevier, 2011)
Mediastinal abscess following retropharyngeal abscess is a rare entity. We report the first neonate presenting with a large mediastinal abscess as a complication of a retropharyngeal abscess. The initial manifestations of this newborn were fever and stridor. The chest sonography revealed a mediastinal mass, and the neck and chest computed tomography showed multiple abscesses in the retropharyngeal space, parapharyngeal space, and superior mediastinum. The mediastinal cystic mass was excised, and antibiotic treatment was completed for 7 weeks. She did well without any sequelae at follow-up clinic. Pediatricians should consider retropharyngeal and mediastinal abscesses among the differential diagnoses when confronting a newborn with fever and stridor.